Achieving Outstanding Schools through Value-Based Digital Leadership to Enhance High Tech and High Touch - Manadin, Ade; Komariah, Aan; Prihatin, Eka; Triatna, Cepi; Salsabil, Syifa Hanifa (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to examine Value-Based Digital Leadership for Achieving Outstanding Schools (High Tech & High Touch) in elementary and junior high schools in Garut Regency. The research employs a mixed-method approach with a sequential explanatory design and utilizes SEM analysis through AMOS software. The study involves supervisors, principals, and teachers as respondents. The results indicate that Value-Based Digital Leadership significantly impacts High Touch, both directly and indirectly, particularly at the junior high school level. Additionally, digital competencies and skills significantly contribute to High Tech. The results demonstrate that Value-Based Digital Leadership significantly contributes to the effectiveness of both High Tech and High Touch components in schools. Specifically, Digital Leader Values, Competence, and Skills were found to have a substantial impact on the implementation of High Technology in schools, with Digital Leader Values showing the strongest influence. The study reveals that the combined effect of these leadership aspects contributes 74.2% to the implementation of High Technology in schools. Moreover, the implementation of High Technology was found to have a direct and significant effect on High Touch, contributing 49.7% to the enhancement of social interaction and emotional support within the educational environment. Recommendations are provided for the Department of Education, supervisors, principals, teachers, and school committees to strengthen digital leadership values and skills and enhance digital infrastructure. This model is expected to create a more interactive and efficient learning environment, keeping pace with modern developments.